Evaluation of the Effectiveness of Islamic Religious Education Programs in Developing Students’ Islamic Understanding - Arifuddin, Arifuddin; Palili, Sampara; Agussalim, Agussalim (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping students’ Islamic understanding and Islamic character, particularly in integrated Islamic schools. This study aims to evaluate the effectiveness of the Islamic Religious Education program in developing students’ Islamic understanding at SMPIT As-Sunnah Makassar. The research employs a qualitative approach using a case study design. Data were collected through observations, in-depth interviews with the school principal, IRE teachers, students, and parents, as well as document analysis. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing, with triangulation techniques used to ensure data validity. The findings indicate that the IRE program at SMPIT As-Sunnah Makassar is holistically designed by integrating the national curriculum and diniyyah curriculum, and is implemented through intrakurikuler learning and non-formal Islamic character development activities. The program has proven effective in enhancing students’ Islamic understanding across cognitive, affective, and psychomotor domains, as reflected in increased religious knowledge, worship skills, and the development of Islamic morals and character. Nevertheless, further optimization is needed in terms of documenting student development and utilizing evaluation technologies. This study is expected to serve as a reference for the development and improvement of the quality of Islamic Religious Education programs in integrated Islamic schools.